The most unique discussion of the 21st century? The debate on the Anthropocene pictured in seven points. (April 2019) - Bińczyk, Ewa
Nineteen years after Stoermer's and Crutzen's proposal, the article poses questions regarding the sources of the captivating uniqueness dwelling in the idea of the Anthropocene and in the debate surrounding it. The distinctiveness of the Anthropocene debate is elucidated in seven points. These points discuss: (1) a shocking confrontation of timeframes, (2) the drama surrounding the risk of losing the future, (3) a bold reinterpretation of the basic philosophical concepts, (4) the unification of different disciplines around a common research agenda, (5) the central problem of irreversibility, (6) the eschatological dimension of the debate, (7) the vision of the debate as a warning and a catalyst for political change.